Bahasa Al Quran dalam Perspektif Politik Kekuasaan - Muradi, Ahmad (ULUL ALBAB Jurnal Studi Islam, 2010)
An interesting part of Quranic studies is sosio-culture of its Quran language. Â Â It becomes notice when Arabic language was chosen as Koran language. The point of view of this study is the political power of Quraisy when Quraisy holding the power in Hijaz territory. The question is: What is the reason of Arabic language (Quraisy language) chosen as Koran language? Is there any relationship between Quraisy and political power Arabic language being chosen as Koran language? Seeing in the historical aspect, the northern Arabic language being survive because is supported by political aspect and arabization. Based on the interaction of Arabic language (Quraisy) standard language (fusha) was appearing. Quraisy political system, although not reflects absolute power that forced another ethnic group, there is a relationship of power factor and why Arabic language chosen as Quran language.